Characterization of a poly(butylene adipate-co-terephthalate) hydrolase from the mesophilic actinobacteria Rhodococcus fascians. (February 2021) - Soulenthone, Phouvilay; Tachibana, Yuya; Suzuki, Miwa; Mizuno, Tsukasa; Ohta, Yukari; Kasuya, Ken-ichi
Highlights: Mesophilic actinobacterium Rhodococcus fascians NKCM2511 biodegrades PBAT. The gene pbathRf responsible for PBAT degradation was cloned from this strain. The protein product of pbathRf, PBATH Rf, degraded PBAT films. PBATH Rf properties enable biodegradation of PBAT in the actual field conditions. Abstract: Poly(butylene adipate- co -terephthalate) (PBAT) possesses excellent film-forming ability and biodegradability. Therefore, it is considered to be a promising mulching film material that eliminates the need for recovery. In the applications that require PBAT degradation in the field after use, it is important to understand the biodegradation mechanism at moderate temperatures. We have previously isolated from the soil the mesophilic actinobacteria Rhodococcus fascians NKCM2511 that biodegraded PBAT under moderate temperature conditions (20–30 °C). In this study, to clarify the mechanism of PBAT degradation by the strain NKCM2511, a DNA fragment carrying the gene pbathRf responsible for the PBAT degradation activity was cloned. The gene encoded a 216-amino-acid-long protein designated as PBATH Rf . Homology modeling revealed that PBATH Rf belongs to the α/β hydrolase fold family, lacking the lid domain covering the active site. PBATH Rf degraded PBAT film at 30 °C at the rate of 0.10 ± 0.03 mg/cm 2 /d and was capable of degrading several other aliphatic polyester films. Liquid chromatography revealed that PBATH Rf preferentially cleaved the ester bond between 1, 4-butanediol and adipic acid rather than that between 1, 4-butanediol and terephthalic acid (T). This characteristic of PBATH Rf may explain the low degradation rate of the aliphatic- aromatic copolyester PBAT, compared to the rate of degradation of aliphatic polyesters without T. In addition, liquid chromatography showed that PBATH Rf released T, mono(2-hydroxyethyl) terephthalic acid, and bis(2-hydroxybutyl) terephthalate from an amorphous poly(ethylene terephthalate) (PET) film. However, no significant change in the PET film surface after the treatment with PBATH Rf was found by scanning electron microscopy. This is the first report of an enzyme from the mesophilic actinobacteria Rhodococcus fascians that can hydrolyze various polyesters, including PBAT, and catalyze hydrolysis on the surface of an amorphous PET film. This study also provides insight into the biodegradation mechanism of PBAT in the actual field as it describes an enzyme from a naturally occurring organism that acts in the medium temperature range.